Frameworks for teacher evaluation in Basic Education: the case of Mexico (Práxis Educativa, 2024)
This study examined two frameworks for teacher evaluation in Mexico established in the educational reforms of 2013 and 2019. The principles of component analysis were applied to identify similarities and distinctions between the two processes. The studied categories included: theoretical perspective, level of abstraction, methodological approach, conception of teaching, assessment strategies, intended uses, and validity evidence. The results reveal structural similarity between both processes; differences in the conception of teaching, competencies, and indicators; and discrepancies between declared use and measurement instruments. Additionally, there is a need for coherence between declared use and practical application, as well as alignment of evaluation criteria and mechanisms with the educational reality of teachers to enable improvement in teaching.Keywords: Basic Education, Teacher evaluation. Professional profile.